Kuantifikasi Mikroorganisme dan Kelayakan Konsumsi Madu Lokal yang Diperjualbelikan di Kabupaten TTS (Timor Tengah Selatan) - Bero, Catharina De Ricci Inye; Sanam, Maxs U. E.; Wuri, Diana A. (JURNAL KAJIAN VETERINER, 2023)
Honey is a product of animal origin with a low water composition but rich in sugar content (fructose and glucose) which is produced through the fermentation process in honey bee hives. This study aims to look at the quantification of microorganisms and the physicochemical quality of local honey which is traded in TTS (South Central Timor) Regency. The testing technique was carried out using the TPC test for total bacterial contamination and total mold and yeast contamination, testing the physical properties of honey using heating and organoleptic testing, and testing the chemical properties of honey which included testing water content, sugar content and pH. The test was carried out on 8 honey samples taken from 3 honey-producing villages in TTS Regency, namely Loli Village, Tobaki Village, and Nenas Village. The results of the total bacteria, mold and yeast test showed that the average bacterial contamination in honey was 7.24×105 and the average mold and yeast contamination was 30.31×105, where these results exceeded the contamination limit according to SNI No.7388:2009, namely the total contamination. bacteria <5×103 colonies/g and total mold and yeast contamination <1×101 colony/g. The physico-chemical properties test was carried out to find that the physical properties of honey were not in accordance with the SNI No.01-3545-2013 and SNI No.8664:2018.